IoT in Physics Experiments to Improve Science Process Skills: A Literature Review - St. Hajar; Ahmad Fauzi; Winda Pratiwi; Gunawan Gunawan; Nina Nisrina (Indonesian, 2024)
The development of digital technology in the Industrial Revolution 4.0 era has encouraged the use of technology in various fields, including physics education. Practical activities play a crucial role in helping students understand abstract physics concepts through hands-on experiments. However, the implementation of physics practicums still faces various obstacles, such as limited laboratory facilities, limited experimental equipment, and manual measurement process, which can potentially lead to measurement errors and limitations in data analysis. This study aims to examine the development of Internet of Things (IoT)-based physics practicum teaching materials, focusing on sensor design, real-time data acquisition systems, and the integration of data analysis into learning. The research method used was a literature review, analyzing various scientific articles published between 2015 and 2024, obtained from scientific databases such as Google Scholar and national and international journals. The results of the study indicate that IoT technology has significant potential to improve the quality of physics practicums through the use of sensors, microcontrollers, and automated data collection systems that enable real-time monitoring of experimental data. Furthermore, the integration of contextual teaching materials and technology-based learning media has been shown to improve conceptual understanding, learning motivation, and student engagement in the learning process.